Mind and morality in Thomas Nagel's philosphy (Diametros, 2004)
In the paper I give an overlook of Thomas Nagel’s moral philosophy, showing its connections with his position in the philosophy of mind. I start with an analysis of Nagel’s argument presented in The Possibility of Altruism and examine the development of his position in his later works. I argue: 1) that the failure of Nagel’s first argument does not imply the failure of his central idea, that is, of the idea of grounding morality in a system of reasons for actions, 2) that the development of Nagel’s moral philosophy results in a better correlation between it and his position in the philosophy of mind, and 3) that Nagel’s later position gives a new insight into the debate between deontological and consequentialist theories in moral philosophy and makes it possible to accommodate the position of those who deny the claims of morality by appealing to an individual’s right to autonomy.